Protector of conscience, proponent of service: General Lewis B. Hershey and alternative service during World War II - Krehbiel, Nicholas A. (Kansas State University, 2009)
The primary figure in the creation and administration of alternative service for conscientious objectors (COs) during World War II was General Lewis B. Hershey, Director of the Selective Service. With an executive order by President Franklin D. Roosevelt placing the responsibility for alternative service on the shoulders of Hershey, any program within Civilian Public Service (the alternative service program for COs) desired by the Historic Peace Churches (Brethren, Mennonite, Society of Friends) needed Hershey’s approval before it could commence. As a product of the National Guard, Hershey possessed a strong belief in the duty of the citizen to the state in a time of national emergency. However, Hershey also had Mennonite ancestry and a strong belief in minority rights. Though not personally religious, all of his beliefs towards religion, duty, minority rights, and service contributed to a much more liberal policy for COs during World War II, compared to the insensitive treatment of them during the First World War. In short, “Protector of Conscience, Proponent of Service” argues that Lewis Hershey held the primary authority for constructing policy concerning conscientious objection during World War II, and his personal beliefs and actions in shaping alternative service during that time established precedent for the remaining years of conscription in the United States. From the initial peacetime draft in 1940 to the end of conscription in 1973, alternative service remained as the central form of a CO’s duty to the state in lieu of serving in the military. Hershey’s beliefs and actions during World War II resulted in a concept of alternative service that remained for the following years of conscription in the United States, providing an illuminating example of how the concept of the citizen soldier evolved in American military history and extended even to those who refused to serve in the military.
Keywords: Lewis B. Hershey; World War II; Conscientious objection; Military history; Civilian Public Service; Historic Peace Churches; History, Modern (0582); History, United States (0337)